Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Pengguna Telkomsel di Kota Palangka Raya - Ahriyati Ahriyati; Puput Iswandiyah Raysharie; Luluk Tri Harinie; Bella Frista; Ahmad Maulana; Febby Agustian; Juntristo Agriva; Marjuliansi Bulan Putri; Muhaimin Muhaimin; Oktavia Riani; Riany Pramawati; Samuel Novrian Thomassoyan; Vicky Krisdian Gestianto (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
Communication is one of the basic things in human life. Communication cannot be separated from human life, because it is a process of interaction between a person or group of people and their environment. In this case, good communication is very influential on the quality of service. The better the quality of service in the company, the higher the achievement of customer satisfaction. At the same time, poor service can undermine customer trust and satisfaction. . The purpose of this study was to determine the relationship between service quality and Telkomsel customer satisfaction in Palangka Raya City. Data collection was carried out by distributing 100 questionnaires to Telkomsel service users in Palangka Raya City who were selected by random sampling. Respondents were asked to provide value or satisfaction points for Telkomsel's service quality. The procedure used in this study is a simple regression procedure with cross section data type. The data obtained was processed using the Eviews 12 application. The results of the data analysis obtained the regression model Y = 15.706 + 0.8041X. From this study it can be concluded that service quality has a positive and significant effect on customer satisfaction.